Influência da exclusão da precipitação na variação mensal da biomassa aérea no Projeto ESECAFLOR - LBA ,Caxiuanã - PA - SIQUEIRA, Ionara Santos (2019)
This research studied the variability of aerial biomass in a rainy tropical forest area in the Amazônia, submitted artificially to water deficiency, with 95% of exclusion, approximately, of water proceeding from rain and an control area (natural) in one hectare of ESECAFLOR Project, located in the Ferreira Penna Scientific Station (ECFPn), in the city of Melgaço, Pará, located on 01º42'30''S and 51º31'W. Were utilized aerial biomass data from the month of June of 2006 till June of 2007, as much for the control parcel (natural area) as for the exclusion parcel. The results had indicated that the biomass in the parcel A (control) was higher than in parcel B (exclusion), having as main justification the exclusion of the rain water, providing great reduction in the water availability in the ground.